Analisis Minat Kunjung Ulang Pasien Non BPJS di Unit Rawat Jalan RS Atma Jaya (Journal of Hospital Management, 2020)
Revisit intention is very important for service industry because maintaining customer’s loyalty for a long term is the key of success for a business including hospital. The purpose of this study was to determine the effect of customer perceived value and brand image on revisit intention of private (non BPJS) patient in Atma Jaya Hospital outpatient unit, with patient’s satisfaction as intervening variable. The author uses survey method with questionnaires instrument spread to 200 samples. Analysis of result was carried out using SEM and illustrated through descriptive statistics. Research findings indicate that customer perceived value and brand image has positive effect on patient’s satisfaction, customer perceived value has positive effect on patient’s revisit intention. However, brand image and patient’s satisfaction have no effect on patient’s revisit intention in Atma Jaya Hospital. By implication, Atma Jaya Hospital has to focus also on another variable for future improvement.Keyword: customer perceived value, brand image, patient satisfaction, patient revisit intention